2011
DOI: 10.1097/dcr.0b013e31822cb5c2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pathophysiology of Functional Constipation Among Women in Catalonia, Spain

Abstract: Functional constipation is extremely prevalent among young, healthy, Spanish women, dyssynergic defecation being the most prevalent subtype. Slow transit constipation without dyssynergic defecation is uncommon. Structural pelvic floor disorders are highly prevalent in middle-aged women with dyssynergic defecation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
4
18
0
3
Order By: Relevance
“…The points for each question were summed. According to the scoring system in the original questionnaire, 0 point refers to not symptomatic, 1-3 points to least symptomatic, 4-7 points to mild symptomatic, [8][9][10][11][12][13][14][15] points to moderately symptomatic and 16 and more points to most symptomatic. The questionnaire was administered prospectively to patients equal and above 18 years that presented to Family Medicine outpatient clinic of Eskisehir Osmangazi University Translation process: The Constipation scale was translated into Turkish by three researchers, and a consensus meeting was held after the translation process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The points for each question were summed. According to the scoring system in the original questionnaire, 0 point refers to not symptomatic, 1-3 points to least symptomatic, 4-7 points to mild symptomatic, [8][9][10][11][12][13][14][15] points to moderately symptomatic and 16 and more points to most symptomatic. The questionnaire was administered prospectively to patients equal and above 18 years that presented to Family Medicine outpatient clinic of Eskisehir Osmangazi University Translation process: The Constipation scale was translated into Turkish by three researchers, and a consensus meeting was held after the translation process.…”
Section: Methodsmentioning
confidence: 99%
“…According to studies conducted in Turkey, the rate of constipation varies between 22-40% (4). According to different studies, it is seen more frequently in women, children and elderly people (5,7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Isolated slow-transit constipation is an unusual cause of chronic constipation, and many patients with slowtransit constipation have concomitant obstructive defecation. 19,20 For example, Ragg et al 19 found that, of 541 patients with chronic constipation, 29% had obstructive defecation plus slow-transit constipation, and only 5% had isolated slow-transit constipation (colonic inertia). However, the optimal treatment for patients with combined slow-transit constipation and obstructive defecation is still unclear.…”
mentioning
confidence: 98%
“…These two pathophysiological changes influence each other, become causes to each other, and form a vicious cycle [1,2]. Many therapies are available, but no unanimous conclusion has been reached.…”
mentioning
confidence: 98%